2018
DOI: 10.1177/0954407018765277
|View full text |Cite
|
Sign up to set email alerts
|

Tyre–road friction μ-estimation based on braking force distribution

Abstract: In this work, we develop a rules-based µ-estimation algorithm which is independent of any tyre model and may be employed independently by brake control systems of the vehicle. The algorithm proposed herein aims at estimating the tyre/road friction coefficient during braking, in particular when one or more of the tyres approach the limit of adhesion. The proposed algorithm avoids the use of any particular tyre model and the need to identify several parameters of such models. It uses measurements of variables th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 26 publications
(41 reference statements)
0
7
0
Order By: Relevance
“…In addition, a rule-based TRFC estimation method was also proposed in Ref. [27], which can still have a good estimation accuracy when the wheels reach the limit of adhesion. Since TRFC varies not only with road conditions but also with tires, the experiment-based real-time TRFC estimation method can further improve the accuracy of TRFC estimation under different driving conditions [28].…”
Section: Longitudinal Dynamics-based Methodsmentioning
confidence: 99%
“…In addition, a rule-based TRFC estimation method was also proposed in Ref. [27], which can still have a good estimation accuracy when the wheels reach the limit of adhesion. Since TRFC varies not only with road conditions but also with tires, the experiment-based real-time TRFC estimation method can further improve the accuracy of TRFC estimation under different driving conditions [28].…”
Section: Longitudinal Dynamics-based Methodsmentioning
confidence: 99%
“…The comparisons suggest that the brush tire model yields force-slip properties comparable to those of the MF model up to about 15% slip, which is considered as a commonly encountered slip range. 26,31 Considering the tire longitudinal stiffness is largely affected by the normal load, 38 the longitudinal stiffness is assumed to be constant when there is only small variation in the tire normal load.…”
Section: Estimation Approach and Tire Modelmentioning
confidence: 99%
“…The vast majority of the aforementioned studies have shown that an accurate estimation of the TRFC necessitates relatively higher magnitude of the disturbance in terms of longitudinal slip ratio or side-slip angle. The previous studies have thus employed maneuvers leading to high magnitudes of longitudinal deceleration 31,32 or lateral acceleration. 24,33 A few studies have even considered sinusoidal steering inputs or severe double-lane change and slalom-type maneuvers for realizing higher lateral acceleration of the vehicle.…”
Section: Introductionmentioning
confidence: 99%
“…Ribeiro et al [5] solved the tire-road friction coefficient estimation method which provided a more efficient method with robust results through the knowledge of lateral tire force. Paul et al [6] developed a rules-based 𝑢-estimation algorithm that was independent of any tire model and was validated through implementation in high-fidelity vehicle dynamics simulation. Focusing on sliding-mode techniques, followed by the development of a novel friction estimation technique, Rajendran et al [7] presented a review of existing estimation methods that was a novel slip-based estimation method and an important tool in developing the next generation ABS systems for electric vehicles.…”
Section: Introductionmentioning
confidence: 99%